Echocardiographic Screening for Rheumatic Heart Disease in Indigenous Australian Children: A Cost–Utility Analysis. Issue 3 (2nd March 2017) - Roberts, Kathryn; Cannon, Jeffrey; Atkinson, David; Brown, Alex; Maguire, Graeme; Remenyi, Bo; Wheaton, Gavin; Geelhoed, Elizabeth; Carapetis, Jonathan R.
Abstract : Background: Rheumatic heart disease (RHD) remains a leading cause of cardiovascular morbidity and mortality in children and young adults in disadvantaged populations. The emergence of echocardiographic screening provides the opportunity for early disease detection and intervention. Using our own multistate model of RHD progression derived from Australian RHD register data, we performed a cost–utility analysis of echocardiographic screening in indigenous Australian children, with the dual aims of informing policy decisions in Australia and providing a model that could be adapted in other countries. Methods and Results: We simulated the outcomes of 2 screening strategies, assuming that RHD could be detected 1, 2, or 3 years earlier by screening. Outcomes included reductions in heart failure, surgery, mortality, disability‐adjusted life‐years, and corresponding costs. Only a strategy of screening all indigenous 5‐ to 12‐year‐olds in half of their communities in alternate years was found to be cost‐effective (incremental cost‐effectiveness ratio less than AU$50 000 per disability‐adjusted life‐year averted), assuming that RHD can be detected at least 2 years earlier by screening; however, this result was sensitive to a number of assumptions. Additional modeling of improved adherence to secondary prophylaxis alone resulted in dramatic reductions in heart failure, surgery, and death; these outcomes improved even further when combined with screening. Conclusions: Echocardiographic screening for RHD is cost‐effective in our context, assuming that RHD can be detected ≥2 years earlier by screening. Our model can be adapted to any other setting but will require local data or acceptable assumptions for model parameters.